Inhibition of Connexin 43 Hemichannels Alleviates Cerebral Ischemia/Reperfusion Injury via the TLR4 Signaling Pathway - Chen, Yingzhu; Wang, Liangzhu; Zhang, Lingling; Chen, Beilei; Yang, Liu; Li, Xiaobo; Li, Yuping; Yu, Hailong (Frontiers in Cellular Neuroscience, 2018)
ABSTRACT Connexin 43(Cx43) widely exists in all components of the neurovascular unit and is a constituent of gap junctions and hemichannels. In physiological states, gap junctions are open for regular intercellular communication, and the hemichannels present low open probability in astrocytes. After cerebral ischemia, a large number of hemichannels are unusually opened, leading to cell swelling and even death. Most known hemichannel blockers also inhibit gap junctions and sequentially obstruct normal electrical cell-cell communication. In this study, we tested the hypothesis that Gap19, a selective Cx43-hemichannel inhibitor, exhibited neuroprotective effects on cerebral ischemia/reperfusion (I/R). An obvious improvement in neurological scores and infarct volume reduction were observed in Gap19-treated mice after brain ischemia induced by middle cerebral artery occlusion (MCAO). Gap19 treatment attenuated white matter damage. Moreover, Gap19 treatment suppressed the expression of Cx43 and TLR4 pathway-relevant proteins and prevented the overexpression of TNF-α and IL-1β. To further explore downstream signaling, we established an in vitro model--oxygen glucose deprivation (OGD) to simulate ischemic conditions. Immunofluorescence staining showed that Cx43 co-existed with TLR4 in astrocytes. The hemichannel activity was increased after OGD and Gap19 could inhibit this effect on astrocytes. Gap19 substantially improved relative cell vitality and decreased the expression of Cx43, TLR4 and inflammatory cytokines in vitro. In addition, in the LPS stimulation OGD model, Gap19 also exhibited a protective effect via inhibiting TLR4 pathway activation. In summary, our results showed that Gap19 exerted a neuroprotective effect after stroke via inhibition of the TLR4-mediated signaling pathway.